Uptake of Cationic PAMAM-PLGA Nanoparticles by the Nasal Mucosa - Mohammed A. Albarki; Maureen D. Donovan (MDPI AG, 2022)
Nanoparticles provide promising advantages in advanced delivery systems for enhanced drug delivery and targeting. The use of a biodegradable polymer such as PLGA (poly lactic-co-glycolic acid) promotes improved nanoparticle safety and, to some extent, provides the ability to modify nanoparticle surface properties. This study compared the effect of altering the surface charge on the translocation of PLGA nanoparticles across excised nasal mucosal tissues. Nanoparticles (average diameter of 60-100 nm) loaded with Nile Red (lipophilic fluorescent dye) were fabricated using a nanoprecipitation method. The effects of nanoparticle surface charge were investigated by comparing the transfer of untreated nanoparticles (negatively charged) and positively charged PLGA nanoparticles, which were modified using PAMAM dendrimer (polyamidoamine, 5th generation). All nanoparticles were able to be transferred in measurable quantities into both nasal respiratory and olfactory mucosae within 30 min. The total nanoparticle uptake was less than 5% of the nanoparticle mass exposed to the tissue surface. The cationic nanoparticles showed a significantly lower transfer into the mucosal tissues where the amount of nanoparticles transferred was 1.8-4-fold lower compared to the untreated negatively charged nanoparticles. The modification of the nanoparticle surface charge can alter the nanoparticle interaction with the nasal epithelial surface, which can result in decreasing the nanoparticle transfer into the nasal mucosa.